Theoretical test using Libras to obtain the National Driver's License: Exploratory usability assessment with interpreters and deaf people - Sá, Felipe Melo Feliciano de; Alves, Lucas Eduardo Melo; Aguiar, Ana Carolina; Aguiar, Yuska Paola Costa (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2024)
The theoretical test system for obtaining the national driver's license (CNH) has a translation service from Portuguese to Brazilian Sign Language (Libras) to promote access for deaf users. This article reports on the usability assessment of the test for CNH integrated with the Libras translation service. The evaluation comprises heuristic usability inspection, exploratory usability testing with deaf users and Libras interpreters, and analysis of responses obtained from participants to the System Usability Scale (SUS). The results show that the most violated heuristics correspond to "Consistency and Standards" and "Error prevention". Also, even for users who responded to the SUS evaluating the system as acceptable (70%), the quality of translations for technical terms, considering the context of traffic legislation, must be improved.